Regulation of dendritic branching by Cdc42 GAPs - Simó, Sergi (Cold Spring Harbor Laboratory Press, 2012)
Nerve cells form elaborate, highly branched dendritic trees that are optimized for the receipt of synaptic signals. Recent work published in this issue of Genes & Development by Rosario and colleagues (pp. 1743–1757) shows that a Cdc42-specific GTPase-activating protein (NOMA-GAP) regulates the branching of dendrites by neurons in the top layers of the mouse cortex. The results raise interesting questions regarding the specification of arbors in different cortical layers and the mechanisms of dendrite branching.